DYNAMIQUE TERRITORIALE À LA FRONTIÈRE BÉNINO-NIGÉRIANE: RÔLE DES MARCHÉS DU SUD-EST TERRITORIAL DYNAMICS ON THE BENINO-NIGERIAN BORDER: ROLE OF THE MARKETS OF THE SOUTHEAST - Sossou-Agbo, Anani Lazare (European Scientific Journal, ESJ, 2013)
The benino-nigerian borders were historically territories of concentration of economic activities between both States. The Southeast is a particular example thanks to the local markets, but also, that of Badagry who was a colonial market at that time. The object of this study is to analyze the economic and social impact of the mobility of the populations on both sides’ borders of the Southeast in the outer-urban and rural development. The socioeconomic factors and the need of big cities as Cotonou and Porto Novo oblige men and women to put a lot into the cross-border exchanges in the daytime and at night by way of tracks and leak. This study was realized during my research works in Benin for the period November, 2008 in September, 2009. It focused on the appropriation of the space by the populations in their mobility in the valley of Oueme. The low valley of Oueme being a complex where river, lake, lagoon, and interminable form a vast deltaïque territory. The work of ground was directed to the carriers of the wet zones generally and those who played a very important role in the transit, the import and the export towards Nigeria (Badagry and Lagos). Three actors held attention during the investigations on the ground: the trading women, the carriers (some rice, the wheat flour and oil productions) and the boatmen of customs posts. Among others, two customs posts served in the study: the post of Ponton; front door lagoon, less checked, with regard to the ground front door of Mededjonou. Three points of accessibility; outer-urban villages (Ponton, Mededjonou and Louho) and a district of the city of Porto-Novo (Acrontokpa) allowed the understanding of the reports which these populations maintain with the territory. Two conversations by village and a participating observation in the markets of Adjarra, from Ouando to Porto Novo and from Dantokpa to Cotonou served in this work. The analysis of the report in the local territory sends back to the approaches in terms of nearness and the permeability of these borders. The study will be interested in markets, in cross-border mobility of the populations and in social factors in these border villages and their influence on the urban economy.